2022
DOI: 10.3389/fpubh.2022.854532
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Social Media Addiction With Internet Use and Perceived Health: The Moderating Effects of Regular Exercise Intervention

Abstract: The popularity of online social media in recent years has not only brought information and social convenience to people's lives, but has also given rise to many problems, among which social media addiction (SMA) has become a concern of many scholars and experts. Past research has shown that regular exercise (REx) can have many health benefits for the body, so numerous scholars and experts believe that this may be one possible strategy for reducing the health effects of online community addiction and Internet u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 84 publications
1
7
0
Order By: Relevance
“…If we consider the edge weights with high and medium as clinically meaningful, our edge weight findings can be interpreted as indicating that there is high comorbidity for gaming with internet use, alcohol with drugs (undifferentiated), and internet use with social media. Consistent with these findings, previous studies have also shown a robust and strong association between internet use with video game addiction (Gunuc, 2015) and social media addiction (Chen et al, 2022) and also alcohol and drugs (Karriker-Jaffe et al, 2018;Kendler et al, 2008;Verweij et al, 2018). Additionally, Kendler et al (2008) have shown that nicotine, alcohol, and cannabis addictive behaviors presented with a similar emergence pattern, with family-related influences playing a significant role in early adolescence and declining/diminishing between 35 and 40 years, while genetic influences/predisposition effects became stronger over the life-course.…”
Section: Implications Of Network Findingssupporting
confidence: 82%
“…If we consider the edge weights with high and medium as clinically meaningful, our edge weight findings can be interpreted as indicating that there is high comorbidity for gaming with internet use, alcohol with drugs (undifferentiated), and internet use with social media. Consistent with these findings, previous studies have also shown a robust and strong association between internet use with video game addiction (Gunuc, 2015) and social media addiction (Chen et al, 2022) and also alcohol and drugs (Karriker-Jaffe et al, 2018;Kendler et al, 2008;Verweij et al, 2018). Additionally, Kendler et al (2008) have shown that nicotine, alcohol, and cannabis addictive behaviors presented with a similar emergence pattern, with family-related influences playing a significant role in early adolescence and declining/diminishing between 35 and 40 years, while genetic influences/predisposition effects became stronger over the life-course.…”
Section: Implications Of Network Findingssupporting
confidence: 82%
“…In the current study, we included active Douyin users who have used Douyin at least 1 h per day in the past month. In this context, a recent study found that physical activity was more effective in improving social media usage among individuals with low levels of social media addiction (66). However, among those with high levels of social media addiction, physical activity may act as a catalyst for increasing social media usage (66).…”
Section: Physical Activitymentioning
confidence: 99%
“…In this context, a recent study found that physical activity was more effective in improving social media usage among individuals with low levels of social media addiction (66). However, among those with high levels of social media addiction, physical activity may act as a catalyst for increasing social media usage (66). To better understand the role of physical activity in improving Douyin usage at bedtime, we recommend that future research conducts a comparative or stratified analysis based on Douyin addiction levels.…”
Section: Physical Activitymentioning
confidence: 99%
“…Students may get restless, irritable, anxious, and crave being online again when trying to cut back on consumption. Students find it difficult to stop using social media because of this addictive cycle, which emphasizes the importance of encouraging sensible usage patterns and digital well-being [54]. There are possible effects on oneʹs academic or professional career, concerns associated with online safety, and effects from social networking platforms.…”
Section: Recommendationmentioning
confidence: 99%